2014
DOI: 10.35818/acta.v9i1.246
|View full text |Cite
|
Sign up to set email alerts
|

Um olhar sobre Ximenia americana L. e suas potencialidades

Abstract: A ameixa-do-mato (Ximenia americana L.) cresce em diversas formações vegetais desde o nível do mar até cotas altitudinais próximas a 2.000m e encontra-se distribuída nos cinco continentes.  Procedeu-se revisão não sistematizada de 39 artigos revisados por pares a fim de elencar as principais partes utilizadas, os usos, as potencialidades e as finalidades dentro das categorias de uso alimentício e medicinal. Os trabalhos mostraram maior evidência para as raízes e para as cascas dos caules utilizadas principalme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Ximenia americana L. is a plant species native to the Brazilian Northeast, especially found in the state of Ceará, where it is popularly known as "ameixa do-mato, ameixabrava ou ameixa-do-sertão" [26,27]. Ethnopharmacological studies revealed that local communities use the bark of this plant to treat diarrhea, pain, fever, virus infections, wounds [28,29], leprotic ulcerations [30] inflammation of the uterus and ovaries, and stomach ulcer [31].…”
Section: Introductionmentioning
confidence: 99%
“…Ximenia americana L. is a plant species native to the Brazilian Northeast, especially found in the state of Ceará, where it is popularly known as "ameixa do-mato, ameixabrava ou ameixa-do-sertão" [26,27]. Ethnopharmacological studies revealed that local communities use the bark of this plant to treat diarrhea, pain, fever, virus infections, wounds [28,29], leprotic ulcerations [30] inflammation of the uterus and ovaries, and stomach ulcer [31].…”
Section: Introductionmentioning
confidence: 99%